Role of oxygenation devices in alleviating the oxygen crisis in India. - Deepshikha Batheja; Vinith Kurian; Sharon Buteau; Neetha Joy; Ajay Nair (Public Library of Science (PLoS), 2023)
There has been an unprecedented increase in global demand for medical oxygen equipment to solve the acute oxygen shortages caused by SARS-CoV-2 infection. The study aims to assess the value of improved access and use of Oxygen Concentrators (OCs) and cylinders during the COVID-19 pandemic in India. This evaluation is relevant to strengthening health systems in many resource-constrained Low- and Middle-Income Country (LMIC) settings. Using a Probability Proportional to Size (PPS) sampling method, primary surveys were conducted in 450 health facilities across 21 states in India. The primary outcomes measured were self-reported utility of oxygenation devices in meeting the oxygen demand in the short-run and long-run utility of devices compared to the pre-oxygen-devices-distribution-period. We perform bivariate and multivariate regression analyses. Around 53-54% of surveyed facilities reported that the distributed oxygenation devices helped meet oxygen demand in the short run and are expected to increase their long-run capacity to admit non-COVID patients with oxygen needs. The timely availability of technicians was associated with meeting oxygen demand using the additional oxygenation devices at the facilities. Facilities that increased the number of staff members who were able to administer oxygen devices were at higher odds of reducing the administrative load on their staff to organize oxygen support in the long run. Hospital infrastructure was also associated with long-run outcomes. We find that oxygenation devices such as cylinders and OCs were useful in addressing the oxygen demand during the COVID-19-related oxygen emergency. Overall production of oxygen to meet the demands and investments in training biomedical engineers/technicians to administer oxygen could help save lives.